The impacts of climate change on water resources and agriculture in China - Piao, Shilong; Ciais, Philippe; Huang, Yao; Shen, Zehao; Peng, Shushi; Li, Junsheng; Zhou, Liping; Liu, Hongyan; Ma, Yuecun; Ding, Yihui; Friedlingstein, Pierre; Liu, Chunzhen; et al. (Nature (London), 2010)
China's growth factor China, since mid-2010 the world's second biggest economy and tipped to become the biggest in a few decades, has tremendous climatic and ecological diversity. The likely impact of China's economic expansion on the global climate has been extensively studied but little is known about the reverse case — the susceptibility of natural and managed systems in China to climate change. In a Review, Shilong Piao et al . assess the impacts of historical and future climate change on water resources and agriculture in China. They find that in spite of clear trends in climate (especially temperature), overall impacts are overshadowed by natural variability and uncertainties in crop responses and projected climate, especially precipitation. In a best-case scenario, crop production is constant, whereas the worst-case scenario suggests that production could fall by about 20% by 2050. China has tremendous climatic and ecological diversity, so the impacts of climate change on natural and managed systems might likewise be expected to be diverse. Yet so far systematic studies have been rare. Here, the impacts of historical and future climate change on water resources and agriculture in China are assessed. Despite clear trends in climate, the overall impacts are overshadowed by natural variability and uncertainties in crop responses and projected climate, especially precipitation. China is the world’s most populous country and a major emitter of greenhouse gases. Consequently, much research has focused on China’s influence on climate change but somewhat less has been written about the impact of climate change on China. China experienced explosive economic growth in recent decades, but with only 7% of the world’s arable land available to feed 22% of the world’s population, China's economy may be vulnerable to climate change itself. We find, however, that notwithstanding the clear warming that has occurred in China in recent decades, current understanding does not allow a clear assessment of the impact of anthropogenic climate change on China’s water resources and agriculture and therefore China’s ability to feed its people. To reach a more definitive conclusion, future work must improve regional climate simulations—especially of precipitation—and develop a better understanding of the managed and unmanaged responses of crops to changes in climate, diseases, pests and atmospheric constituents.